Does Aconitum septentrionale chemically protect floral rewards to the advantage of specialist bumblebees?. (20th May 2013) - GOSSELIN, MATTHIAS; MICHEZ, DENIS; VANDERPLANCK, MARYSE; ROELANTS, DOROTHÉE; GLAUSER, GAETAN; RASMONT, PIERRE
<x xml:space="preserve">Abstract</x> Chemical protection of plants against herbivory is a well‐studied phenomenon. However, chemical protection of floral rewards remains relatively unexplored. As with herbivore–plant interactions, toxic rewards may impact generalist and specialist foragers in different ways. This study focuses on the toxic plant Aconitum septentrionale (Ranunculaceae). This plant is visited by specialist and generalist bumblebees. Alkaloid concentrations and profiles for the different parts of A. septentrionale were analysed to detect a potential chemical toxicity of floral rewards. In the same way, sequestration of alkaloids was tested on a pollen specialist species Bombus consobrinus and a generalist species Bombus wurflenii. A liquid chromatography‐quadrupole time‐of‐flight mass spectrometry method was developed to discriminate 16 major compounds in the plant. These alkaloids were present in all parts of the plant, but in different ratios. The concentration was high in the roots but also in pollen, providing evidence of chemical protection of this reward. By contrast, nectar had the lowest concentration of alkaloids. Only six alkaloids were detected in B. consobrinus tissues, at trace levels. For the generalist bumblebee B. wurflenii, no traces of alkaloids were detected. Lappaconitine was the major alkaloid compound in pollen, nectar and B. consobrinus tissues. Low accumulation of alkaloids in B. consobrinus tissues could be an ecological advantage for this specialist species in terms of pathogen and predatory avoidance.